ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Kushendri Kushendri; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to determine the extent of high school students' mathematical problem solving abilities. The method used in this study is descriptive with a qualitative approach. The population in this study were all high school students in West Bandung Regency, while the sample was 20 students of class XI in one of the high schools in West Bandung Regency. The results obtained from this study indicate that the percentage of indicators 3 chooses and applies strategies to solve mathematical problems or outside mathematics and indicator 4 explains or interprets the results according to the problem and checks the correctness of the results or answers, gets the lowest percentage with 60% and 31%. Then the students' mistakes in solving the problem of mathematical problem solving ability lies in the process of selecting and implementing a calculation strategy and students have not been able to elaborate on the strategies that will be carried out to carry out the next calculation. Based on the results of student answers, it can be said that the level of problem solving ability of students in one of the high schools is quite sufficient even though they still have many difficulties in working on the questions on indicators 3 and 4.